2015 23rd European Signal Processing Conference (EUSIPCO) 2015
DOI: 10.1109/eusipco.2015.7362503
|View full text |Cite
|
Sign up to set email alerts
|

Row-shift corrected truncation of paraunitary matrices for PEVD algorithms

Abstract: In this paper, we show that the paraunitary (PU) matrices that arise from the polynomial eigenvalue decomposition (PEVD) of a parahermitian matrix are not unique. In particular, arbitrary shifts (delays) of polynomials in one row of a PU matrix yield another PU matrix that admits the same PEVD. To keep the order of such a PU matrix as low as possible, we pro- pose a row-shift correction. Using the example of an iterative PEVD algorithm with previously proposed truncation of the PU matrix, we demonstrate that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 9 publications
0
65
0
Order By: Relevance
“…I. Two roots at z = −2 and z = − 1 2 match closely, but do not entirely coincide due to estimation errors by the SMD algorithm as well as due to trimming of the polynomial matrix factors [14]. As a results, root finding algorithms such the one in [25] cannot determine the GCD exactly, and roots here have been matched by inspection.…”
Section: Numerical Examplementioning
confidence: 92%
See 1 more Smart Citation
“…I. Two roots at z = −2 and z = − 1 2 match closely, but do not entirely coincide due to estimation errors by the SMD algorithm as well as due to trimming of the polynomial matrix factors [14]. As a results, root finding algorithms such the one in [25] cannot determine the GCD exactly, and roots here have been matched by inspection.…”
Section: Numerical Examplementioning
confidence: 92%
“…(M − 1) will still form valid eigenvectors satisfying (8). This allpass filter must be common to all elements of q m (z), and can in the simplest case form a delay [14]. Note that therefore q m (z) and q ′ m (z) will have an identical magnitude but different phase responses.…”
Section: A Existencementioning
confidence: 99%
“…Since current PEVD algorithms can be shown to either favour or can even be proven to yield spectral majorisation (McWhirter and Wang, 2016), they result in matrix factors with high polynomial order to approximate the factors in (5). Therefore, some mechanisms to curb the order of these polynomial (Foster et al, 2006) and specifically the paraunitary factors (Ta and Weiss, 2007b;McWhirter et al, 2007;Corr et al, 2015c;Corr et al, 2015d) have been suggested, which are generally based on a truncation with limited error impact, and in some cases judiciously exploit the arbitrary phase response of the eigenvectors.…”
Section: Algorithms For Polynomial Matrix Evdmentioning
confidence: 99%
“…In this paper we use the recently developed row-shift corrected truncation method [11], this approach takes advantage of an ambiguity in the paraunitary matrix to further reduce its polynomial order.…”
Section: General Anatomymentioning
confidence: 99%